Comparing Methods for Cardiac Output: Intraoperatively Doppler-Derived Cardiac Output Measured With 3-Dimensional Echocardiography Is Not Interchangeable With Cardiac Output by Pulmonary Catheter Thermodilution. (August 2018) - Graeser, Karin; Zemtsovski, Mikhail; Kofoed, Klaus F.; Winther-Jensen, Matilde; Nilsson, Jens C.; Kjaergaard, Jesper; Møller-Sørensen, Hasse
Abstract : BACKGROUND: Estimation of cardiac output (CO) is essential in the treatment of circulatory unstable patients. CO measured by pulmonary artery catheter thermodilution is considered the gold standard but carries a small risk of severe complications. Stroke volume and CO can be measured by transesophageal echocardiography (TEE), which is widely used during cardiac surgery. We hypothesized that Doppler-derived CO by 3-dimensional (3D) TEE would agree well with CO measured with pulmonary artery catheter thermodilution as a reference method based on accurate measurements of the cross-sectional area of the left ventricular outflow tract. METHODS: The primary aim was a systematic comparison of CO with Doppler-derived 3D TEE and CO by thermodilution in a broad population of patients undergoing cardiac surgery. A subanalysis was performed comparing cross-sectional area by TEE with cardiac computed tomography (CT) angiography. Sixty-two patients, scheduled for elective heart surgery, were included; 1 was subsequently excluded for logistic reasons. Inclusion criteria were coronary artery bypass surgery (N = 42) and aortic valve replacement (N = 19). Exclusion criteria were chronic atrial fibrillation, left ventricular ejection fraction below 0.40 and intracardiac shunts. Nineteen randomly selected patients had a cardiac CT the day before surgery. All images were stored for blinded post hoc analyses, and Bland-Altman plots were used to assess agreement between measurement methods, defined as the bias (mean difference between methods), limits of agreement (equal to bias ± 2 standard deviations of the bias), and percentage error (limits of agreement divided by the mean of the 2 methods). Precision was determined for the individual methods (equal to 2 standard deviations of the bias between replicate measurements) to determine the acceptable limits of agreement. RESULTS: We found a good precision for Doppler-derived CO measured by 3D TEE, but although the bias for Doppler-derived CO by 3D compared to thermodilution was only 0.3 L/min (confidence interval, 0.04–0.58), there were wide limits of agreement (−1.8 to 2.5 L/min) with a percentage error of 55%. Measurements of cross-sectional area by 3D TEE had low bias of −0.27 cm 2 (confidence interval, −0.45 to −0.08) and a percentage error of 18% compared to cardiac CT angiography. CONCLUSIONS: Despite low bias, the wide limits of agreement of Doppler-derived CO by 3D TEE compared to CO by thermodilution will limit clinical application and can therefore not be considered interchangeable with CO obtained by thermodilution. The lack of agreement is not explained by lack of agreement of the 3D technique.